A feasibility study on Green Leaf Paper Company - Buenaventura, Luis III (College of Engineering, 2001)
Paper recycling is already a common practice in most countries, including the Philippines. Recycling not only reduces large volumes of waste paper, but also, indirectly contributes to the slowing down of deforestation. However, the quality of recycled paper is often lower than that made from virgin wood pulp because of impurities. The most common impurity is the ink or toner that is used to print or write on paper. In order to remedy this, manufacturers often use bleach to whiten the recycled paper. Recent studies have shown that the use of bleach in paper manufacturing can release a harmful chemical to the environment called dioxin. It may be ingested by fish and other animals, and ultimately by humans, through the hierarchy of the food chain. Dioxin levels at only ten times the amount that can be found in a person can cause such health problems as cancer. A possible solution to this problem is to remove toner and ink particles that are in the used paper before they are recycled without using bleach. A recently conducted study shows that the enzyme of Trichoderma reesei, a fungus that is very common in the Philippines, performs effectively as a toner remover. The group proposes to conduct a study on the feasibility of setting up a paper recycling company that employs the use of this enzyme in place of bleach as whitening agent. The results of the market study show that there is a favorable market potential for bleach-free recycled paper. A survey conducted by the group yielded a high acceptability rating (77%) for the proposed product. Analysis of the past demand and supply trends and their future projections show that there is an increasing demand-supply gap for bond paper in the Philippines. The company will initially attempt to fulfill a small fraction of this unsatisfied demand and attempt to increase its market share by gradually increasing production and employing appropriate marketing strategies. A proposed five-year marketing strategy plan shows that a budget of approximately 7.5 million pesos will be required.